THE SPATIAL PATTERN OF THE AVAILABILITY AND NEEDS RATIO OF RICE IN LEBAK REGENCY, BANTEN PROVINCE - Maria Hedwig Dewi Susilowati; Dewi Susiloningtyas; Ratri Candra Restuti; Adi Wibowo (GEOMATE Journal, 2020)
Rice is a staple food for a population of Lebak Regency, Banten Province. The needs of rice in the Lebak Regency are increasing along with the increase in population. The problem of availability of rice for each village in the Lebak Regency does not meet the population needs of each village. The purpose of this study is to analyze: (1) Spatial differences of the ratio of the availability and requirements of rice; (2) The correlation between physical factors (elevation, slope, drought, forest area) and non-physical (population density, distance from the center of district capital of Lebak Regency) to the ratio of the availability and needs of rice. The analytical method used in this study is spatial analysis and statistical analysis (Pearson product-moment). The results and discussion showed: (1) Spatially, there are differences in the region ratio of the availability and needs of rice. The deficit region was located in the north, close to the district capital; (2) The correlation between physical and non-physical factors with the ratio of availability and needs of rice is not significant at the significance level (α) = 0.05, which means that the surplus area of rice is not always in the same physical and non-physical area. The conclusion of this research that’s the deficit and surplus area of rice is not always in the same physical and non-physical area